Teologi Politik Islam; Membaca Konstruksi Teologi Politik Hassan Hanafi Dan Abed Al-Jabiri - Rizky HK, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2021)
This article will discuss the theological basis of politics in Islamic tradition, based on Hassan Hanafi an Abed al-Jabiri’s view. Islam, as a system of belief was born and developed historically in very thick socio-political background. Islamic political identity can be traced through historical trajectories and comprehensive reading of the crystallization of theological dogmas. This article attempts to examine the theological constructs carried by two Islamic reformers, Hassan Hanafi and Abed al-Jabiri. Hassan Hanafi comes with a new challenge to western political ideas, especially secularism, through systemic notes on Islamic tradition, or in another sense, viewing the west with Islamic eyes. Meanwhile al-Jabiri came up with an offer of ontological renewal which views that Islam does exist as both a worldly and a religious conception. This article attempts to concoct these two thoughts as part of an effort to read political reality from a theological point of view.